Technical review of JKR's "Handbook on seismic design guidelines for concrete buildings in Malaysia" - Jeffrey, Chiang, Dr.; Hee, M. C. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/